A density-based contention window control scheme for unicast communications in vehicular ad hoc networks. (2017) - Balador, Ali; Calafate, Carlos; Cano, Juan-Carlos; Manzoni, Pietro
Achieving a well-designed medium access control (MAC) protocol is a challenging issue to improve communications efficiency due to the dynamic nature of vehicular ad hoc networks (VANETs). IEEE 802.11p standard was selected as the best choice for vehicular environments considering its availability, maturity, and cost. The common problem in all IEEE 802.11 based protocols is scalability, exhibiting performance degradation in highly variable network scenarios. Experimental results for the IEEE 802.11-based MAC protocol show the importance of contention window adjustment on communications performance; however the vehicular communications community has not yet addressed this issue in unicast communication environments. This paper proposes a novel contention window control scheme for VANET environments based on estimating the network density, which is then used to dynamically adapt the CW size. Analysis and simulation results show that our proposal provides better overall performance compared with previous proposals, even in high network density scenarios.